Design and build a pond temperature control system and automatic feed for tilapia in aquaponics - Aisyah, Putri Yeni; Widya Pratama, I Putu Eka; Permadani, Dyah Ayu (Faculty of Vocational Studies - Research Center, DRPM ITS, 2024)
Expansion of land causes the population and food needs to be unbalanced. One way to overcome this problem is aquaponic cultivation. Aquaponics is a modern practical farming system that integrates plant cultivation systems with the cultivation of aquatic animals. One of the success factors of aquaponics is temperature and automatic feeding of pond water. To get the right temperature for fish, temperature control can be done using the DS18B20 temperature sensor. When the fish pond temperature drops below 28°C, the heater will automatically turn on to raise the pond temperature, and when the pond temperature rises above 32°C, the peltier will light up and start lowering the fish pond temperature. Automatic feeding uses the Real Time Clock (RTC) module as a timer and a servo motor as the opening valve for the fish feed container. The results of this research obtained the relative growth rate (RGR) ratio of fish before and after the control system was installed was 7.14% and 11.2%, respectively. The feed conversion ratio (FCR) values of fish before and after the control system was installed were 12.50% and 21.07%, respectively. The plant growth rate before and after the control system was installed were 22.9% and 33.71%, respectively.